"Effect of milk thistle addition (Silybum Marianum L.) on marinated herring (Clupea Harengus L.) meat". Issue 7 (8th March 2021) - Ochrem, Andrzej; Kułaj, Dominika; Pokorska, Joanna; Żychlińska-Buczek, Justyna; Zapletal, Piotr; Drąg-Kozak, Ewa; Łuszczek-Trojnar, Ewa
Abstract : Purpose: The aim of the study was to analyse the quality changes in marinated herring meat depending on the moment of adding milk thistle. Design/methodology/approach: One control (C) and two experimental groups were investigated: MH (milk thistle added to a marinade solution) and FH (fillets rubbed with milk thistle before marination). The basic chemical composition, the meat colour, heavy metals concentration, fatty acids profile, quality of lipids and antioxidant capacity were determined. Findings: The occurrence of Fe, Mn, Cu and Zn was higher in the experimental group than in the control group throughout the marinating process. The peroxide value was higher from the first day in the control group than in the experimental groups. On the last day of the study, the peroxide value in the control group exceeded the maximum acceptable value. The highest level of Thiobarbituric Acid Reactive Substances was determined in the control group on the first day, and the lowest in the FH group. On the first day, the highest percentage of DPPH (2, 2-Diphenyl-1-picrylhydrazyl) radical quenching was recorded in the FH group. Originality/value: The results are the first to find that the addition of milk thistle to herring fillets in marinating process maintains or even improves the quality of the marinades. The process of previously coating the fillets in milk thistle and then marinating achieves a lower peroxide value, higher content of polyunsaturated fatty acids and a higher content of elements such as iron and manganese, which are very valuable for human health.